TEACHING READING COMPREHENSION BY USING K.W.L GRAPHIC ORGANIZER TECHNIQUE TO THE EIGHTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL OF BINA JAYA PALEMBANG - Ria, Nita; Ilma, Ridha (English Education Study Program Universitas Muhammadiyah Palembang, 2017)
This study aimed to find out whether or not there was any significant difference in reading comprehension between the eighth grade students of Bina Jaya Junior High School Palembang who were taught by using K.W.L graphic organizer technique and those who were not. Seventy-two eighth graders were the sample of the study.The writers did an experimental method by using quasi-experimental design to the two groups of students. The VIII.3 class became the experimental group and the VIII.2 class was the control group. A reading comprehension test was an instrument to collect the data. The result found that the significant level was 0.000 < 0.05, so that (Ha) was accepted and (Ho) was rejected. So, there was a significant difference on studentsÃ¢â¬â¢ reading comprehension between the eighth grade students of Bina Jaya Junior High School Palembang who were taught by using KWL Graphic Organizer and those who were not.